Smartphones and Varsity Athletes: A Complicated Relationship - Poppy DesClouds; Natalie Durand-Bush (Frontiers Media S.A., 2021)
Varsity athletes are a group of high performers situated within a demographic notable for smartphone usage and media-multitasking. Surprisingly, little research has examined the impact of smartphones in the lives of varsity athletes. The purpose of this exploratory, qualitative study was to begin addressing this gap by investigating varsity athletes' experiences with smartphones. Varsity athletes (n = 21) from nine different sports participated in one of five focus groups, and data emerging from these discussions were subjected to an inductive thematic analysis. Results indicate that smartphones are a mainstay of varsity athletes' experiences, as the athletes regularly use their smartphones to manage roles and demands across multiple contexts (e.g., sport, school, home). Themes pertained to concurrent negative (e.g., stress, distraction, disengagement) and positive (e.g., self-regulation, social connectedness) implications of smartphone usage, making it clear that athletes' relationship with their smartphone is a complicated one. Findings contribute to the limited studies of smartphone usage among athletes, and support the notion that implications of usage exist along a continuum, rather than in distinct categories of "good" and "bad". Results can inform practical guidelines for optimising athletes' use of smartphones in and around the sport context.